Persons and Sovereigns in Ethical Thought - Ladelle McWhorter (Genealogy, 2017)
Contemporary concepts of moral personhood prevent us from grappling effectively with contemporary social, political, and moral problems. One way to counter the power of such concepts is to trace their lineage and shifting political investments. This article presents a genealogy of personhood, focusing on the crisis of both personhood and sovereignty in seventeenth-century England. It demonstrates the optionality of personhood for moral thinking and exposes personhood’s functions in political dividing practices.